Impact of time from diagnosis to treatment on erectile function outcomes after radical prostatectomy. (3rd September 2019) - Schifano, N.; Capogrosso, P.; Pozzi, E.; Ventimiglia, E.; Cazzaniga, W.; Matloob, R.; Gandaglia, G.; Dehò, F.; Briganti, A.; Montorsi, F.; Salonia, A.
Abstract: Background: Concerns exist about the effect of delaying treatment for prostate cancer (PCa) regarding both oncological and functional outcomes after radical prostatectomy (RP). Objective: To assess the impact of time from diagnosis to RP on post‐operative erectile function (EF) outcomes. Materials and methods: We analyzed data for 827 patients treated with RP at a single center from 2002 to 2017. The International Index of Erectile Function‐EF (IIEF‐EF) was compiled by every patient (EF recovery equal to IIEF‐EF ≥ 22). Time from diagnosis to treatment was defined as the interval between biopsy and RP. Cox regression analysis was used to test the impact of time to surgery on the probability of EF recovery. Kaplan–Meier analysis compared the cumulative incidence of EF recovery according to time from diagnosis to surgery. The impact of time to RP on EF was tested also in a sub‐cohort of patients eligible for active surveillance (AS). Results: Overall, low‐, intermediate‐, and high‐risk PCa was found in 306 (37%), 422 (51%), and 99 (12%) patients. Of them, 148 (17.9%) would have been eligible for AS. A total of 152 (18%) and 22 (2.7%) patients were treated after 6 and 12 months from diagnosis. The overall probability of EF recovery was 32% (95% CI: 29–36) at 24 months. Cox regression analysis showed that time from biopsy to surgery was not associated with a different chance of EF recovery (HR: 1.01; 95% CI: 0.97–1.05; p  = 0.7). At Kaplan–Meier analysis, the cumulative incidence of EF recovery did not differ between patients treated within 6 months, from 6 to 12 months and after 12 months from diagnosis. Similar findings were obtained for patients eligible for AS. Discussion: Patients may be reassured regarding their chance of post‐operative EF recovery in the case of a delayed surgical treatment. Conclusions: Delaying surgery after PCa diagnosis does not affect post‐operative EF recovery outcomes regardless of oncological risk.